PERTANGGUNGJAWABAN PERUSAHAAN TERKAIT KARYAWANNYA YANG TER-PHK AKIBAT DARI PANDEMI COVID 19 BESERTA PERLINDUNGAN HUKUMNYA - Leonardus Lintang Pratama (2022)
2020 was a tough year, Indonesia and even the world was hit by a wave of the Covid- 19 pandemic. With this pandemic, the President of the Republic of Indonesia, Mr. Insyur Joko Widodo, issued Presidential Decree No. 12 of 2020 concerning establishing Covid-19 as a national disaster. With this presidential decree, it can be implied that the Covid-19 pandemic is a force majeure event. The existence of this presidential decree and force majeure is the reason for the company to unilaterally terminate the employment relationship, without also fulfilling the rights of the laid-off workers. This paper is written to find out whether the Covid- 19 pandemic is a force majeure that can be an excuse for employers to unilaterally terminate employment. As well as to find out also the rights obtained by workers after the termination of employment carried out by the company refers to the related article. The research method used is a normative juridical method with a statutory approach and a conceptual approach. The results of this study indicate that the Covid-19 pandemic is a force majeure, but if it is associated with the related articles, employers cannot automatically terminate their employment on the grounds that the Covid-19 pandemic is a force majeure, but it must still be seen whether the company is have suffered losses for 2 consecutive years. As well as protection for workers affected by layoffs in the form of severance pay, award money or service fees during the worker's working period.